Cultivating Healthy Eating, Exercise, and Relaxation (CHEER): A Case Study of a Family-Centered and Mindfulness-Based Cognitive-Behavioral Intervention for Obese Adolescents at Risk for Diabetes and Cardiovascular Disease. (June 2014) - Sperry, Steffanie; Knox, Brian; Edwards, Denise; Friedman, Andrea; Rodriguez, Mario; Kaly, Perry; Albers, Michelle; Shaffer-Hudkins, Emily
Attrition from weight management programs and difficulty maintaining success are of significant concern for pediatric overweight patients. Patient and family variables associated with completing and maintaining outcomes from a healthy weight program include understanding and buy-in for treatment, parental motivation, and valuing of weight loss to quality of life. Such findings highlight the need for comprehensive intervention that involves family members and addresses motivation and relapse prevention. The present study describes a family-centered and mindfulness-based cognitive-behavioral intervention implemented with a 15-year old, clinically obese male with associated symptoms including elevated blood pressure and sleep apnea. This pilot implementation resulted in improved pre–post outcomes in regard to weight, blood pressure, and health-promoting behaviors. Improvements in healthy lifestyle were maintained 1-year post-treatment. These results add to the growing literature on ecologically relevant intervention for obese adolescents at risk for future health complications. Technical issues and clinical implications related to recruitment and retention are discussed.